2013
DOI: 10.3892/br.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

Association of IP-10 gene polymorphism with susceptibility to Enterovirus 71 infection

Abstract: Abstract. Enterovirus 71 (EV71) often causes large outbreaks of diseases among children worldwide and its pathogenesis remains unclear. The aim of the present study was to investigate the association between interferon-inducible protein 10 (IP-10) polymorphism in children with EV71 infection. Polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) were performed to analyze the gene polymorphisms of IP-10 (-1596C/T) in 58 EV71-infected and 48 control patients. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Variants of type II IFN and other chemokines also contributed to EV71 HFMD. Interferon gamma induced proteins-10 (IP-10) gene −1596 T was the risk factor of EV71 infection 20 . Interleukin 10 (IL-10) and interferon gamma (IFN-γ) gene SNPs were associated with the susceptibility to EV71 HFMD encephalitis 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variants of type II IFN and other chemokines also contributed to EV71 HFMD. Interferon gamma induced proteins-10 (IP-10) gene −1596 T was the risk factor of EV71 infection 20 . Interleukin 10 (IL-10) and interferon gamma (IFN-γ) gene SNPs were associated with the susceptibility to EV71 HFMD encephalitis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of type I IFN signaling pathway genes like MX1 and OAS1 have been reported to link to the occurrence and development of HFMD 18 19 . Other variants of type II IFN related genes IFN-γ, IL-10 and IP-10, chemokines CCL2 and CXCL10 and eNOS also contributed to susceptibility or severity to EV71 infection 20 21 22 23 .…”
mentioning
confidence: 99%
“…In EV71-infected HFMD patients, the levels of IP-10 were significantly elevated as compared to healthy controls [24]. The association between IP-10 polymorphism in children and EV71infection has been studied [46]. The result showed that the frequency of carrying CT+TT genotype (10.3) and T allele (6.0%) in EV71infected cases was significantly lower than that of the controls (29.2 and 15.6%), which indicated that IP-10-1596 T allele may be a beneficial factor for EV71 infection.…”
Section: Chemokinesmentioning
confidence: 99%
“…CYP19A1 gene polymorphism is associated with reduced aromatase activity, which can lead to the development of endometriosis (Wang et al, 2010;Zaree et al, 2015;Hosseini et al, 2016;Abu Hashim, 2016). While previous studies have investigated the association between CYP19A1 and risk of endometriosis, the results were inconsistent (Hur et al, 2007;Vietri et al, 2009;Yang et al, 2010;Szczepańska et al, 2013;Wang et al, 2012Wang et al, , 2014. We have shown that there is a significant correlation between CYP19A1 rs2899470 and risk of endometriosis in a Chinese population.…”
Section: Discussionmentioning
confidence: 69%